Strong Directional Source Effect and Coping Strategy in Passive Data Detection - Yuefeng Yan; Shaodong Jing; Jiao Wang; Xuedong Ma; Xiaozhong Liu; Xu Zhang; Liu Liu; Wei Fang (IEEE Access)
In passive source exploration, seismic records are typically assumed to satisfy the equipartition condition. However, in urban environments, buildings and factories act as strong, directionally biased seismic sources, causing recorded signals to deviate from equipartition. To investigate this effect, we numerically simulate seismic records received by orthogonal arrays under varying source distributions. The influence of the wavefield propagation direction is analyzed by MUSIC (multiple signal classification), energy-phase velocity curves, and extracted dispersion. Our results demonstrate that strong directional sources introduce significant discrepancies in energy-phase velocity spectra across different array orientations. However, optimizing the observation system can mitigate this effect. When the illumination angle between two receivers sufficiently covers the dominant propagation directions, the extracted dispersion aligns more closely with theoretical predictions. We carry out the field test in Qingdao with the L-shaped array. Because of the influence of the village and factories, the recorded data also show the same phenomena. Dispersion obtained by linear arrays in different directions are not accurate. The observation system should be optimized and the illumination of the estimated two receivers’ path should cover the propagation directions. Therefore, it is necessary to design new observation system and calculate the illumination of the two receivers’ path to obtain accurate dispersion data in passive source exploration.